A Rigid Trigonal‐Prismatic Hexagold Metallocage That Behaves as a Coronene Trap. Issue 20 (4th April 2019) - Ibáñez, Susana; Peris, Eduardo
Abstract: A trigonal‐prismatic hexagold cage was obtained by combining a triphenylene‐tris(N‐heterocyclic carbene) ligand and a carbazolyl‐bis(alkynyl) linker. The metallocage has a slot‐like cavity with a volume of about 300 Å 3 . The cage was used for the recognition of several polycyclic aromatic hydrocarbons. Due to the perfect dimensional match, the supramolecular complex shows a very high affinity for trapping coronene. Abstract : Gotcha ! A trigonal‐prismatic hexagold cage with a slot‐like cavity was obtained by combining a triphenylene‐tris(N‐heterocyclic carbene) ligand and a carbazolyl‐bis(alkynyl) linker. It can be used for the recognition of several polycyclic aromatic hydrocarbons and shows a perfect dimensional match for the trapping of coronene.